Development and validation of a 30-item short adaptation of the Mood and Anxiety Symptoms Questionnaire (MASQ) - Wardenaar, Klaas J.; van Veen, Tineke; Giltay, Erik J.; de Beurs, Edwin; Penninx, Brenda W.J.H.; Zitman, Frans G. (Psychiatry research, 2010)
The original Mood and Anxiety Symptoms Questionnaire (MASQ) is a 90-item self-report, designed to measure the dimensions of Clark and Watson's tripartite model. We developed and validated a 30-item short adaptation of the MASQ: the MASQ-D30, which is more suitable for large-scale psychopathology research and has a clearer factor structure. The MASQ-D30 was developed through a process of item reduction and grouping of the appropriate subscales in a sample of 489 psychiatric outpatients, using a validated Dutch translation, based on the original English MASQ, as a starting point. Validation was done in two other large samples of 1461 and 2471 subjects, respectively, with an anxiety, somatoform and/or depression diagnosis or no psychiatric diagnosis. Psychometric properties were investigated and compared between the MASQ-D30 and the full (adapted) MASQ. A three-dimensional model (negative affect, positive affect and somatic arousal) was found to represent the data well, indicating good construct validity. The scales of the MASQ-D30 showed good internal consistency (all alphas > 0.87) in patient samples. Correlations of the subscales with other instruments indicated acceptable convergent validity. Psychometric properties were similar for the MASQ-D30 and the full questionnaire. In conclusion, the MASQ-D30 is a valid instrument to assess dimensional aspects of depression and anxiety and can easily be implemented in psychopathology studies.